A Grateful Heart Breeds Job Satisfaction: The Effect of Gratitude on Job Satisfaction among Honorary Teachers - Destiana Rachmawati; Nurul Qomariyah (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
Apart from civil servants, which hold the status of full-time and permanent employees, there are other type of government employees, called